Housing decisions of older Australians - Productivity Commission (Melbourne, 2015)
The Commission’s flagship research paper An Ageing Australia: Preparing for the Future identified that many older Australians are asset rich but income poor, and flagged challenges for government budgets stemming from the ageing of Australia’s population. In its second flagship research paper, Housing Assistance and Employment in Australia, the Commission investigated the link between housing decisions and government assistance. This, the third flagship research paper, continues the investigation of issues relating to the ageing of Australia’s population, this time focusing on the housing choices made by older Australians. It considers available statistical evidence on the financial and accommodation aspects of housing decisions and draws out some of the policy issues affecting the wellbeing of older Australians and the broader community. The report examines the policies affecting the supply and cost of residential aged care and other age-specific housing, the influence of the tax and transfer system on housing decisions, and the issues in using home equity release to support living standards in retirement. In reaching its conclusions, the Commission drew on evidence from a survey of older Australians conducted on its behalf. Along with Superannuation Policy for Post-Retirement, these reports should support informed discussion and policy formulation to enhance national welfare in an environment of an ageing Australian population.
Commission research papers
Keywords: Ageing; Housing; Ageing; Housing, communities and neighbourhoods; Ageing; Housing; Housing, community and neighbourhoods; Ageing